2018
DOI: 10.3390/jof4040134
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Candida albicans Activity of Thiazolylhydrazone Derivatives in Invertebrate and Murine Models

Abstract: Candidiasis is an opportunistic fungal infection with Candida albicans being the most frequently isolated species. Treatment of these infections is challenging due to resistance that can develop during therapy, and the limited number of available antifungal compounds. Given this situation, the aim of this study was to evaluate the antifungal activity of four thiazolylhydrazone compounds against C. albicans. Thiazolylhydrazone compounds 1, 2, 3, and 4 were found to exert antifungal activity, with MICs of 0.125–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Although these compounds showed antifungal activity, the authors observed an LD 50 < 10mg/kg. This low toxicity was confirmed by a hemolysis assay performed using human erythrocytes [98].…”
Section: In Vivo Toxicity Screeningmentioning
confidence: 68%
“…Although these compounds showed antifungal activity, the authors observed an LD 50 < 10mg/kg. This low toxicity was confirmed by a hemolysis assay performed using human erythrocytes [98].…”
Section: In Vivo Toxicity Screeningmentioning
confidence: 68%
“…The genus Candida has been extensively studied in the G. mellonella model especially for the evaluation of virulence and antifungal efficacy [10,71,72]. G. mellonella was used to test the efficacy of different antifungal compounds against Candida yeasts including conventional antifungal drugs [13][14][15][16][17][18][19][20][21][22][23], new drugs [25][26][27][30][31][32]34] or non-antifungal compounds in a repurposing perspective [24,28,29,33]. Antifungal combinations against Candida spp.…”
Section: Candida Sppmentioning
confidence: 99%
“…Several drugs, such as atorvastatin, a cholesterol-lowering agent [24], miltefosine, an anti-leishmanial drug [33], miramistin, an antiseptic [29], and pilocarpine, a muscarinic agonist [28] were evaluated in a repurposing perspective. In other instances, new synthetic compounds or natural products were tested in vivo in the model [25][26][27][30][31][32]34]. It must be noticed that in all cases, larvae were infected with C. albicans.…”
Section: New Drugsmentioning
confidence: 99%
“…Among these are newly synthesized imidazole derivatives, which have been found to prevent Candida biofilm formation and disrupt existing biofilms (Ribeiro et al, 2014;Gabriel et al, 2019). Thiazolylhydrazone derivatives have also recently emerged as effective antifungal compounds with low mammalian cell toxicity (Cruz et al, 2018).…”
Section: Preventing Candida Biofilms Using Surface Modification With mentioning
confidence: 99%
“…Among these are newly synthesized imidazole derivatives, which have been found to prevent Candida biofilm formation and disrupt existing biofilms ( Ribeiro et al, 2014 ; Gabriel et al, 2019 ). Thiazolylhydrazone derivatives have also recently emerged as effective antifungal compounds with low mammalian cell toxicity ( Cruz et al, 2018 ). 2,6-Bis[(E)-(4-pyridyl)methylidene]cyclohexanone, an antiparasitic compound, was also found to exhibit antifungal properties including the inhibition of Candida filamentation, crucial in biofilm formation ( de Sá et al, 2018 ).…”
Section: Preventing Candida Biofilms Using Surfacementioning
confidence: 99%